2016
DOI: 10.1248/bpb.b15-00611
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Tumor Metastases Cause Enhanced PEGylated Liposome Uptake by Kupffer Cells

Abstract: Kupffer cells in livers bearing tumor metastases were found to have promoted tumor invasion and exacerbated the metastasis. This implies that the function of Kupffer cells might differ between animals bearing hepatic metastases and those that are healthy. Kupffer cells are considered responsible for the accumulation of liposomes in the liver. In this study, we hypothesized that the alteration in the function of Kupffer cells by hepatic metastasis would also affect the biodistribution of liposomes following int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“… 74 Despite its pro-metastatic effect, KCs would eliminate the circulatory liposomes, which were thought to be responsible for liposomal chemotherapy resistance. 82 In that, the depletion of KCs in liver microenvironment would be a possible strategy to inhibit the progression of liver metastasis and improve treatment resistance. Clodronate has been found to kill the host macrophages upon phagocytosis.…”
Section: Liver Tumor Microenvironment Targeted Lnp Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“… 74 Despite its pro-metastatic effect, KCs would eliminate the circulatory liposomes, which were thought to be responsible for liposomal chemotherapy resistance. 82 In that, the depletion of KCs in liver microenvironment would be a possible strategy to inhibit the progression of liver metastasis and improve treatment resistance. Clodronate has been found to kill the host macrophages upon phagocytosis.…”
Section: Liver Tumor Microenvironment Targeted Lnp Strategiesmentioning
confidence: 99%
“…Another possible Kupffer cell-targeting strategy was the use of liposomal oxaliplatin. Ukawa et al 82 found that the injection of liposomal oxaliplatin would decrease the number of KCs without injury to normal hepatocytes. Regarding liposomal RNAi therapy, Pattipeiluhu et al 80 found that RNAi-containing anionic LNPs would specifically target KCs evidenced by threefold targeting enhancement in murine KCs compared to murine hepatocytes.…”
Section: Liver Tumor Microenvironment Targeted Lnp Strategiesmentioning
confidence: 99%
“…In the metastatic hepatic cancer, KCs taking up liposomes were significantly increased, and PEGylated can reverse this result through a reduction in tumor-supportive KCs [189]. Primary pancreatic tumor cells release exosomes that contain migration inhibitory factor (MIF) into the blood circulation.…”
Section: Kupffer Cells In Liver Cancer and Metastasesmentioning
confidence: 99%
“…Brain metastases are malignant tumors in the brain, which have been transferred from other organs; the majority are originally transferred from the lungs and these tumors make up 20-40% of all brain metastases (1). Patients with brain metastases typically have a poor prognosis (1-year overall survival rate of ~60%) (2), however combined modality therapy may improve their overall survival rate (3).…”
Section: Introductionmentioning
confidence: 99%